O estudo da circunferência no ensino médio: uma proposta utilizando um software livre - Vecchi, Gabriel Rosaboni [UNESP] (2015)
This paper seeks to understand what is expected of the teacher in his practice, analyzing o cial documents and material support (school and other books), checking what they can o er for lessons, focusing on the study of the circle. Along with these materials, new possibilities are found with the use of digital technologies, always present and inseparable from the daily lives of the majority of students in elementary and high school. Thus, we present a proposal to use a free educational software as motivation for the study of the circumference, speci cally the study of angles (in radians) in the second year of high school